An Oil Spill Contribution Factors by Shipping Activities: A Preliminary Case Study at Four Marine Authority Levels in Penang - Ismila Che Ishak; Rahmat Hazim Mohalid (International Journal of Supply Chain Management, 2018)
Shipping event is found as an influential and positive force which donates to huge global trading activities. The sea transportation actions contribute to sea problem, especially on oil spill. There are several factors donating to an oil spill problem at sea. However, this research emphasis on two factors which are on human factors and technical factors. The scope of research focuses at Penang Port and Government related bodies. A semi structured interview was conducted among respondents from law enforcement and government related bodies which comprises of Agency Penguat Kuasaan Marin Malaysia, Environment Department, Penang Port Authorities and Marine Department. Upon approval, only five main respondents were interviewed from 26 total samples and population who are among middle level of management from different related government agencies. The human factor elements caused an oil spill comprises of inadequate knowledge, fatigue, lack of training and misunderstanding throughout ship operation. Meanwhile, the technical factor elements comprise of bad weather at sea, old on board equipment, ship do not enter the dock and system failure. The result shows the oil spill is significantly caused by human factors, especially by the lack of training at 18%, fatigue among crew for 18%, inadequate knowledge among crew at 18%, crew misunderstanding of ship operation at 16%, old equipment at 9%, system failure at 9%, bad weather at 9% and finally only 3% due to ship which do not enter the dock.